Three-Dimensional Physical Model in Urologic Cancer - Xie, Yu; Wu, Guanlin; Liang, Yu; Fan, Gang (Frontiers in Surgery, 2022)
Three-dimensional (3D) printing, as an evolving technology, enables the creation of patient-specific physical models with high precision; thus, it is widely used in various clinical practices, especially urologic cancer. There is an increasing need to clarify the contribution of 3D printing in the practice of urological cancer in order to identify various applications and improve understanding its benefits and challenges in clinical practice. Researches have focused on the use of 3D-printed models in patient and trainee education, surgical simulation, as well as surgical planning and guidance. This mini review will present the most recently published studies on the topic, including the applications of 3D-printed models, feasibility of performed procedures, possible simulated organs, application outcomes, and challenges involved in urologic cancer, to provide potential directions for future research.